Enhancement Of Illumination For Medical Image Processing And Early Detection Of Lesions - Alali, Dr. Abdulla Mousa Falah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Video and image are widely used in screening and diagnostic tests of the eyes. But sometimes, due to insufficient lighting, the quality of video or image decreases, which will limit the amount of useful information that we can get from the video images, or worse, it may render the sample inadequate for reading and diagnosis. If we want to maximize the amount of useful information extracted from the video, we must enhance the video image and analyze it. In this topic, we review an algorithm that will possibly solve the illumination problems encountered in such cases.